Overkilling: A specific type of homicide – Constructing the definition: Injuries and victim. (November 2022) - Kopacz, Paweł; Juźwik-Kopacz, Ewa; Bolechała, Filip; Strona, Marcin; Konopka, Tomasz
Highlights: Overkill, homicide, forensic medicine, autopsy, definition. Abstract: Overkilling in the Forensic Medicine field is known as a specific type of homicide where the number of inflicted injuries greatly surpasses the number of fatal ones. Conducted research aimed to create a unified definition of the phenomenon and its classification criteria by analysing a vast majority of data concerning its various characteristics. From the population of homicide victims autopsied in the authors' research facility a number of 167 cases were chosen consisting of both overkilling and other homicides. 70 cases were thoroughly analysed based on the completed court files, autopsy protocols and photographs. First part of the research concerned the facts regarding the injuries sustained and the victim's characteristics. Conclusions of the statistical analysis allowed to characterize overkilling as a type of homicide where the number of injuries (sharp or blunt) is several times higher than the number of fatal injuries. Sharp force injuries predominate, and are often localized on the torso, neck and limbs, while blunt force injuries are localized mostly on the head. There is no significant dominance between the sexes of the victims, mostly they are in their 40-50′s. Victims with reduced abilities to resist predominated (mostly women), which is correlated with the position of their body (lying or sitting) at the begging of the incident. Also overkilling victims more often suffer from defensive injuries and post mortem trauma.